Caracterização estrutural e das propriedades hiperfinas de compostos UO2-Eu2O3 sinterizados - Ivashita, Flávio Francisco (2006)
In this investigation, UO2-Eu2O3 sintered ceramics were structurally characterized to verify the homogeneity of the (U,Eu)O2 solid solution reacted in the solid state. The samples were prepared by mixing the UO2 and Eu2O3 precursors, in the compositions x = 4, 7 and 10% wt. europia. From this powder mixture, cylindrical shaped pellets were further annealed, during a thermal cycle, with and without interruption, conducted up to 1750°C, in reducing atmosphere. The prepared materials were characterized, mainly, by X-ray diffractometry and 151Eu Mössbauer spectroscopy. The resulting phases were identified from the X-ray diffractograms, which were analyzed by the Rietveld method. The results showed that, for samples treated up to 900ºC, europia remains un-reacted, as accordingly revealed by the respective Mössbauer spectra. However, increasing the temperature up to 1300ºC revealed, after 1h of annealing, the formation of a mixed oxide phase, with the urania structure, and the remanence of a fraction of precursor urania. For the most severe heat treatment condition, i.e., after 1h at 1750°C, the europia dissolved completely in urania. At this point, europium occupies the cubic site of uranium in the urania lattice. It was also verified that the lattice parameter of the (U,Eu)O2 solid solution decrease with the initial europia content. Preliminary measurements showed that the thermal diffusivity in the sintered pellets decreased with temperature and the initial europia content.